Coordination Challenges in Scaled Agile - Westerberg, Niklas; Hansson, Olle (My University, 2021)
The automotive industry is experiencing increased pressure for speed and flexibility while also seeing exponential growth of software influence in their products. To manage these challenges, many actors turn their attention to the software industry’s ways of working. The adoption of agile methods has the potential to deliver significant value, but coordination challenges remain when scaling agile. This thesis assists in the struggle by identifying and describing coordination issues experienced between teams across organisational boundaries within companies facing agile transformations. A case study investigating coordination between teams across an organisational interface at Volvo Cars was conducted concurrently with a literature review of agile coordination challenges and potential solutions to these. The literature review revealed research young in its tracks and an absence of conceptual frameworks to analyse coordination challenges. To facilitate analysis of the empirical findings, a segmentation of described challenges was made together with a synthesised list of mechanisms that could potentially be used to overcome these challenges. The case study uncovered seven types of coordination challenges at Volvo Cars. These challenges were not unique to Volvo Cars specific context and could, to a varying extent, be connected to the coordination challenges identified in the literature. Furthermore, it was concluded that most of the challenges extend beyond the scaled agile domain. In some cases, challenges were remnants from before the agile transformation or results of the transformation itself rather than being linked to agile ways of working. The thesis presents an overview of different agile mechanisms and solution ideas that can potentially mitigate the coordination challenges identified. However, more research is warranted for more concrete guidelines on the classification of issues and implementation of solutions. Finally, simply transforming an organisation to follow agile ways of working will not automatically solve coordination – agile provides a toolbox of mechanisms for coordination across interfaces, but practitioners need to choose, combine, and adapt these mechanisms to fit their unique context.
Keywords: Scaling Agile; Coordination in Agile; Agile Coordination; Coordination Challenges; Agile in Automotive; Agile for OEMs; Agile in Industry; Agile Enterprise